Literature Review: Faktor-Faktor yang Mempengaruhi Proses Penyembuhan Luka Kaki Gangren pada Penderita DM Tipe 2 - Stefhanie, Adelia; Wahdini, Rizqa; Roslianya, Nia (Pustaka Galeri Mandiri, 2025)
Type 2 diabetes mellitus is a chronic metabolic disease characterized by impaired glucose regulation, which, if poorly managed, can lead to serious complications such as gangrenous foot ulcers. These ulcers can reduce patients' quality of life, increase the risk of amputation, and prolong hospitalization. The wound healing process in patients with type 2 diabetes is influenced by various interrelated factors. This study aims to identify and analyze the factors that influence the healing process of gangrenous foot ulcers in patients with type 2 diabetes mellitus. This study used a systematic literature review method based on the PRISMA guidelines. Articles were retrieved from databases such as PubMed, Cochrane, and Scopus using relevant keywords. Eight articles that met the inclusion criteria were analyzed based on study design, population, and topic relevance. The study found five main factors affecting wound healing in gangrenous diabetic foot ulcers: age, gender, wound stage, blood glucose control, and duration of wound care. These factors are interconnected and significantly impact the speed and success of wound healing. A comprehensive understanding of these factors is essential for healthcare providers in designing appropriate interventions and improving the effectiveness of wound care in patients with type 2 diabetes mellitus.